Setting up the Biosciences Eastern and Central Africa Hub in Nairobi: A Personal Odyssey - Persley, Gabrielle J. (International Livestock Research Institute, 2011)
Biosciences eastern and central Africa (BecA) is a regional research platform located in Nairobi, Kenya, that was officially launched in 2010. The BecA Hub gives scientists and students from across the region access to state-of-the-art facilities in the life sciences. Gabrielle Persley, who served as senior advisor to the director general of the International Livestock Research Institute (ILRI) for many years, describes her multi-year odyssey as she and others nursed the BecA Hub project at ILRI from the drawing board through political deliberations and, finally, into a brand spanking new laboratory complex on ILRI’s campus.